Pengetahuan, Manfaat, Motivasi, Pengaruh Pengetahuan Investasi, Manfaat, Dan Motivasi Terhadap Minat Berinvesatasi di Pasar Modal Syariah ( Studi Kasus Pada Mahasiswa Univestitas Pamulang) - Suci Annisa; Adam Sugiarto (Jurnal Literasi Akuntansi, 2023)
This study aims to determine the effect of investment knowledge, benefits and motivation on interest in investing in the Islamic capital market. The independent variables used in this study are investment knowledge, benefits, and motivation, and the dependent variable used is the interest in investing in the Islamic capital market. This research is a quantitative research with an associative approach seen from the type of data and analysis. This study used a purposive sampling method. The sample in this study were Pamulang University students with 92 respondents. The data analysis technique in this study used multiple linear regression analysis with a statistical test tool or application, namely the Statistical Package For Social Science (SPSS) version 25. Based on the test, it is known that Investment Knowledge, Benefits, and Motivation simultaneously influence Interest in Investing in the Capital Market Sharia. This study also shows that Investment Knowledge, Benefits, and Motivation have a partial effect on Interest in Investing in the Islamic Capital Market.